Assuming the equation is:
![\frac{x}{2}-\frac{10x-25}{10}=3(x+3)-(x-14)](https://tex.z-dn.net/?f=%5Cfrac%7Bx%7D%7B2%7D-%5Cfrac%7B10x-25%7D%7B10%7D%3D3%28x%2B3%29-%28x-14%29)
When fractions involve numeric denominators, the fractions can be removed by multiplying (both sides) by the LCM of the denominators.
Here the denominators are 2 and 10, hence the LCM is 10.
Multiply by 10 on both sides, not forgetting to distribute when multiplying on the right side:
![10\frac{x}{2}-10\frac{10x-25}{10}=10*3(x+3)-10(x-14)](https://tex.z-dn.net/?f=10%5Cfrac%7Bx%7D%7B2%7D-10%5Cfrac%7B10x-25%7D%7B10%7D%3D10%2A3%28x%2B3%29-10%28x-14%29)
simplify, remember that there are always implied parentheses around numerators and denominators:
![5x-(10x-25)=30(x+3)-10(x-14)](https://tex.z-dn.net/?f=5x-%2810x-25%29%3D30%28x%2B3%29-10%28x-14%29)
Now, distribute, i.e. remove parentheses and distribute:
5x-10x+25=30x+90-10x+140
Simplify
-5x+25=20x+230
transpose terms
25-230=20x+5x
solve
x=-205/25=-41/5
In this particular case, we can also take advantage of the term
(10x-25)/10=5(2x-5)/10=(2x-5)/2 which greatly simplifies the solution process, because the LCM will then be 2 instead of 10.
If we do that, the solution will be:
Multiply by 2 on both sides, not forgetting to distribute when multiplying on the right side:
![\frac{x}{2}-\frac{10x-25}{10}=3(x+3)-(x-14)](https://tex.z-dn.net/?f=%5Cfrac%7Bx%7D%7B2%7D-%5Cfrac%7B10x-25%7D%7B10%7D%3D3%28x%2B3%29-%28x-14%29)
simplify, remember that there are always implied parentheses around numerators and denominators:
![2\frac{x}{2}-2\frac{2x-5}{2}=2*3(x+3)-2(x-14)](https://tex.z-dn.net/?f=2%5Cfrac%7Bx%7D%7B2%7D-2%5Cfrac%7B2x-5%7D%7B2%7D%3D2%2A3%28x%2B3%29-2%28x-14%29)
![x-(2x-5)=6(x+3)-2(x-14)](https://tex.z-dn.net/?f=x-%282x-5%29%3D6%28x%2B3%29-2%28x-14%29)
Now, distribute, i.e. remove parentheses and distribute:
![x-2x+5=6x+18-2x+28](https://tex.z-dn.net/?f=x-2x%2B5%3D6x%2B18-2x%2B28)
Simplify
-x+5=4x+46
solve
5-46=4x+x
-41=5x
x=-41/5
with the same results.